2013
DOI: 10.1007/s11745-013-3832-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat in Relation to Erythrocyte Fatty Acid Composition in Men

Abstract: Erythrocyte membrane fatty acid (EMFA) composition is used in the validation of food frequency questionnaires (FFQ) and the evaluation of dietary fat quality. In this cross-sectional study we aimed to investigate associations of diet with EMFA. Altogether, 1,033 randomly selected Finnish men, aged from 47 to 75 years filled in a FFQ and their EMFA composition was analyzed. Marine polyunsaturated fatty acid (PUFA) intake correlated positively with erythrocyte eicosapentaenoic and docosahexaenoic acids (rs = 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 50 publications
7
48
0
Order By: Relevance
“…The results were obtained using a rather simple dietary assessment method. As in previous studies, a clear relationship between fish intake and EPA and DHA was noted (2,7,10,15,25,31,32) . In these studies, fatty acids were measured either in adipose tissue, whole blood, erythrocytes, platelets, serum or plasma and where either total or fractions of cholesterol, phospholipids and triglycerides were considered.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results were obtained using a rather simple dietary assessment method. As in previous studies, a clear relationship between fish intake and EPA and DHA was noted (2,7,10,15,25,31,32) . In these studies, fatty acids were measured either in adipose tissue, whole blood, erythrocytes, platelets, serum or plasma and where either total or fractions of cholesterol, phospholipids and triglycerides were considered.…”
Section: Discussionsupporting
confidence: 83%
“…The most consistent findings are for fish intake. In these studies, fish intake was associated with blood 20:5n-3 (eicosapentaenoic acid; EPA) and 22:6n-3 (docosahexaenoic acid; DHA), particularly in populations with high intake of fish such as the Japanese (2)(3)(4) and Nordic populations (5)(6)(7)(8)(9)(10) . Studies that investigated whether fats from intake of dairy products associate with blood or adipose tissue fatty acid composition have identified a relationship between fats from dairy products and tissue or blood levels of odd-chained saturated 15:0 (pentadecanoic acid) and 17:0 (heptadecanoic acid), particularly in Swedish populations (11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in concentrations between the groups were not significant statistically p 0.09 Table 2 . Docosahexaenoic acid concentrations reported in this study were in agreement with some previous reports 13 as well as lower than that reported in other studies 19,22,23,27,29,30 .…”
Section: Unsaturated Fatty Acidssupporting
confidence: 93%
“…The effects of fatty acids intake on erythrocyte membrane are well documented [34]. That is why diet was partially-controlled in this research.…”
Section: Discussionmentioning
confidence: 99%